Inverse spectral problem for some generalized Jacobi Hermitian matrices - Ivasiuk, I. Ya. (Methods of Functional Analysis and Topology, 2009)
In this article we will investigate an inverse spectral problem for three-diagonal block Jacobi type Hermitian real-valued matrices with "almost" semidiagonal matrices on the side diagonals.